I greet you this day,
These are the solutions to WASSCE past questions on Sequences.
The link to the video solutions will be provided for you. Please
subscribe to the YouTube channel to be notified of upcoming livestreams. You are welcome to ask questions during
the video livestreams.
If you find these resources valuable and helpful in your passing the
Mathematics test of WASSCE, please consider making a donation:
Google charges me for the hosting of this website and my other
educational websites. It does not host any of the websites for free.
Besides, I spend a lot of time to type the questions and the solutions well.
As you probably know, I provide clear explanations on the solutions.
Your donation is appreciated.
Comments, ideas, areas of improvement, questions, and constructive
criticisms are welcome.
Feel free to contact me. Please be positive in your message.
I wish you the best.
Thank you.
Symbols and Formulas: Arithmetic Sequence
$AS_n$ = $nth$ term of an Arithmetic Sequence
$a$ = first term
$p$ = last term
$d$ = common difference
$n$ = number of terms
$SAS_n$ = sum of the first $n$ terms of an Arithmetic Sequence
$
(1.)\:\: AS_n = a + d(n - 1) \\[5ex]
(2.)\:\: AS_n = vn + w \:\:where\:\: v = d \:\:and\:\: w = a - d \\[5ex]
(3.)\:\: p = a + d(n - 1) \\[5ex]
(4.)\:\: SAS_n = \dfrac{n}{2}(a + AS_n) \\[7ex]
(5.)\:\: SAS_n = \dfrac{n}{2}(a + p) \\[7ex]
(6.)\:\: SAS_n = \dfrac{n}{2}[2a + d(n - 1)] \\[7ex]
(7.)\:\: n = \dfrac{2 * SAS_n}{a + p} \\[7ex]
(8.)\:\: n = \dfrac{p - a + d}{d} \\[7ex]
(9.)\:\: n = \dfrac{-(2a - d) \pm \sqrt{(2a - d)^2 + 8d*SAS_n}}{2d} \\[7ex]
(10.)\;\; d = \dfrac{(p - a)(p + a)}{2 * SAS_n - p - a}
$
Symbols and Formulas: Geometric Sequence
$GS_n$ = $nth$ term of a Geometric Sequence
$a$ = first term
$p$ = last term
$r$ = common ratio
$n$ = number of terms
$SGS_n$ = sum of the first $n$ terms of a Geometric Sequence
$S_{\infty}$ = sum to infinity of a Geometric Sequence
(3.) The third and sixth terms of a Geometric Progression (G.P) are $\dfrac{1}{4}$ and $\dfrac{1}{32}$
respectively.
Find the:
(i) first term and the common ratio
(ii) seventh term
(4.) The fifth term of an Arithmetic Progression (A.P) is 11 and the eighth term is 20
Find the:
(i) 12th term
(ii.) Sum of the first 12 terms
$
AS_n = a + d(n - 1) \\[3ex]
AS_{5} = a + 4d \\[3ex]
11 = a + 4d \\[3ex]
a + 4d = 11...eqn.(1) \\[3ex]
AS_{8} = a + 7d \\[3ex]
20 = a + 7d \\[3ex]
a + 7d = 20...eqn.(2) \\[3ex]
eqn.(2) - eqn.(1) \implies \\[3ex]
(a + 7d) - (a + 4d) = 20 - 11 \\[3ex]
a + 7d - a - 4d = 9 \\[3ex]
3d = 9 \\[3ex]
d = \dfrac{9}{3} \\[5ex]
d = 3 \\[3ex]
From\;\; eqn.(1) \\[3ex]
a = 11 - 4d \\[3ex]
a = 11 - 4(3) \\[3ex]
a = 11 - 12 \\[3ex]
a = -1 \\[3ex]
(i) \\[3ex]
AS_{12} = a + 11d \\[3ex]
= -1 + 11(3) \\[3ex]
= -1 + 33 \\[3ex]
= 32 \\[3ex]
(ii) \\[3ex]
SAS_n = \dfrac{n}{2}(a + AS_n) \\[5ex]
SAS_{12} = \dfrac{12}{2}(-1 + AS_{12}) \\[5ex]
= \dfrac{12}{2}(-1 + 32) \\[5ex]
= 6(31) \\[3ex]
= 186
$
(5.) The second, fourth and sixth terms of an Arithmetic Progression (AP) are $x - 1$, $x + 1$, and 7
respectively.
Find the
(i) common difference;
(ii) first term;
(iii) value of x
$
(i) \\[3ex]
AS_n = a + d(n - 1) \\[3ex]
AS_2 = a + d = x - 1...eqn.(1) \\[3ex]
AS_4 = a + 3d = x + 1...eqn.(2) \\[3ex]
AS_6 = a + 5d = 7...eqn.(3) \\[3ex]
eqn.(2) - eqn.(1) \implies (a + 3d) - (a + d) = (x + 1) - (x - 1) \\[3ex]
a + 3d - a - d = x + 1 - x + 1 \\[3ex]
2d = 2 \\[3ex]
d = \dfrac{2}{2} \\[5ex]
d = 1 \\[3ex]
(ii) \\[3ex]
From\:\: eqn.(3) \\[3ex]
a + 5d = 7 \\[3ex]
a = 7 - 5d \\[3ex]
Subst.\:\: d = 1 \\[3ex]
a = 7 - 5(1) \\[3ex]
a = 7 - 5 \\[3ex]
a = 2 \\[3ex]
(iii) \\[3ex]
From\:\: eqn.(1) \\[3ex]
a + d = x - 1 \\[3ex]
x - 1 = a + d \\[3ex]
x = a + d + 1 \\[3ex]
Subst.\:\: a = 2 \:\:and\:\: d = 1 \\[3ex]
x = 2 + 1 + 1 \\[3ex]
x = 4
$
(6.) The 3rd, 4th and 5th terms of an exponential sequence are x, y, and z respectively.
Which of the following statements is true?
(7.) The difference between the third and first terms of a Geometric Progression (G.P) is 42.
If the fourth term is greater than the second term by 168, find the:
(i) first term
(ii) fourth term
of the progression.
(9.) The sum of the first ten terms of an Arithmetic Progression (A.P) is 130
If the fifth term is 3 times the first term, find the:
(a.) common difference
(b.) first term
(c.) number of terms of the A.P if the last term is 28
$
(a.) \\[3ex]
SAS_n = \dfrac{n}{2}[2a + d(n - 1)] \\[5ex]
SAS_{10} = \dfrac{10}{2}[2a + d(10 - 1)] \\[5ex]
130 = 5[2a + 9d] \\[3ex]
\dfrac{130}{5} = 2a + 9d \\[3ex]
26 = 2a + 9d \\[3ex]
2a + 9d = 26...eqn.(1) \\[3ex]
AS_n = a + d(n - 1) \\[3ex]
AS_5 = a + d(5 - 1) \\[3ex]
AS_5 = a + 4d \\[3ex]
But\;\; AS_5 = 3 * a \\[3ex]
\implies 3a = a + 4d \\[3ex]
3a - a = 4d \\[3ex]
2a = 4d \\[3ex]
\dfrac{2a}{2} = \dfrac{4d}{2} \\[5ex]
a = 2d...eqn.(2) \\[3ex]
Subst.\;\;eqn.(2)\;\;into\;\;eqn.(1) \\[3ex]
2(2d) + 9d = 26 \\[3ex]
4d + 9d = 26 \\[3ex]
13d = 26 \\[3ex]
d = \dfrac{26}{13} \\[5ex]
d = 2 \\[5ex]
(b.) \\[3ex]
Subst.\;\; d = 2\;\;into\;\; eqn.(2) \\[3ex]
a = 2d \\[3ex]
a = 2(2) \\[3ex]
a = 4 \\[5ex]
(c.) \\[3ex]
last\;\;term = p = 28 \\[3ex]
n = \dfrac{p - a + d}{d} \\[5ex]
n = \dfrac{28 - 4 + 2}{2} \\[5ex]
n = \dfrac{26}{2} \\[5ex]
n = 13
$
(10.) If $(3 - x),\;\; 6,\;\; (7 - 5x)$ are consecutive terms of a Geometric Progression with constant ratio
r > 0, find the:
(i) values of x;
(ii) common ratio
(11.) Find the sum of the Arithmetic Progression (AP) $1, 3, 5, ..., 101$
This is a sequence of odd numbers
So, we are asked to find the sum of the first $n$ odd numbers
We need to find the number of terms first
We can find $n$ in two ways.
Mentally
There are 5 oddnumbers from 1 – 10 (1, 3, 5, 7, 9)
There are 6 oddnumbers from 1 – 11 (1, 3, 5, 7, 9, 11)
Therefore, there are 50 odd numbers from 1 – 100
So, there are 51 odd numbers from 1 – 101
$
n = 51 \\[3ex]
\underline{By\:\: Formula} \\[3ex]
a = 1 \\[3ex]
p = 101 \\[3ex]
d = 3 - 1 = 2 \\[3ex]
n = \dfrac{p - a + d}{d} \\[5ex]
n = \dfrac{101 - 1 + 2}{2} \\[5ex]
n = \dfrac{102}{2} \\[5ex]
n = 51 \\[3ex]
$
We can also find $SAS_n$ in two ways.
You may use any of the formulas for $SAS_n$
(12.) The first term of an Arithmetic Progression (A.P) is 31 and the common difference is 9
Show that the nth term is 9n + 22
Hence, find the 20th term.
(13.) The nth term of a sequence is $5 + \dfrac{2}{3^{n - 2}}$ for $n \ge 1$.
What is the sum of the fourth and fifth terms?
Leave your answers in the form $\dfrac{x}{y}$ where x and y are integers.
(15.) If $\dfrac{1}{2}$, $\dfrac{1}{x}$, $\dfrac{1}{3}$ are successive terms of an arithmetic progression
(A.P),
show that $\dfrac{2 - x}{x - 3} = \dfrac{2}{3}$
(19.) The heights of students in a class form an Arithmetic Progression (A.P.) such that the tallest student
is 1.90 m.
The common difference in their heights is 0.05 m and the sum of their heights is 23.25 m.
(a.) How many students are in the class?
(b.) Find the height of the shortest student.
Let:
height of the tallest student = last term = p
height of the shortest student = first term = a
commom difference = d
number of students in the class = number of terms = n
sum of the arithmetic sequence = SASn
$
p = 1.90\;m \\[3ex]
d = 0.05\;m \\[3ex]
SAS_n = 23.25 \\[5ex]
p = a + d(n - 1) \\[3ex]
1.9 = a + 0.05(n - 1) \\[3ex]
a + 0.05n - 0.05 = 1.9 \\[3ex]
a + 0.05n = 1.9 + 0.05 \\[3ex]
a + 0.05n = 1.95 ...eqn.(1) \\[5ex]
SAS_n = \dfrac{n(a + p)}{2} \\[5ex]
23.25 = \dfrac{n(a + 1.9)}{2} \\[5ex]
n(a + 1.9) = 2(23.25) \\[3ex]
an + 1.9n = 46.5 ...eqn.(2) \\[5ex]
\underline{\text{Substitution Method}} \\[3ex]
From\;\;eqn.(1) \\[3ex]
a = 1.95 - 0.05n ...eqn.(3) \\[5ex]
\text{Substitute eqn.(3) into eqn.(2)} \\[3ex]
n(1.95 - 0.05n) + 1.9n = 46.5 \\[3ex]
1.95n - 0.05n^2 + 1.9n = 46.5 \\[3ex]
-0.05n^2 + 3.85n - 46.5 = 0 \\[3ex]
\text{Multiply both sides by } -100 \\[3ex]
-100(-0.05n^2 + 3.85n - 46.5) = -100(0) \\[3ex]
5n^2 - 385n + 4650 = 0 \\[3ex]
\text{Divide both sides by 5} \\[3ex]
n^2 - 77n + 930 = 0 \\[3ex]
(n - 15)(n - 62) = 0 \\[3ex]
n - 15 = 0 \;\;\;OR\;\;\; n - 62 = 0 \\[3ex]
n = 15 \;\;\;OR\;\;\; n = 62 \\[3ex]
\text{Substitute these values of n in eqn.(3)} \\[3ex]
For\;\;n = 15 \\[3ex]
a = 1.95 - 0.05(15) \\[3ex]
a = 1.95 - 0.75 \\[3ex]
a = 1.2 \\[5ex]
For\;\;n = 62 \\[3ex]
a = 1.95 - 0.05(62) \\[3ex]
a = 1.95 - 3.1 \\[3ex]
a = -1.15 \\[3ex]
$
The height of the shortest student, a cannot be a negative value
So, we have to discard that value.
This also implies that the corresponding value of n will be discarded.
Therefore:
(a.) The number of students in the class is 15
(b.) The height of the shortest student is 1.2 m
(27.) (a.) How many numbers between 75 and 500 are divisible by 7?
(b.) The 8th term of an Arithmetic Progression (A.P.) is 5 times the third term while the 7th term is 9
greater than the 4th term.
Write the first five terms of the A.P.
How many numbers between $75$ and $500$ are divisible by $7$?
Between $75$ and $500$ typically means that $75$ and $500$ are not included
Even if they are, both numbers are NOT divisible by $7$
So, we need to find the number immediately greater than $75$ that is divisible by $7$
That number is $77$.
This implies that $77$ is the first term.
Also, we need to find the number immediately less than $500$ that is divisible by $7$
That number is $497$.
This implies that $497$ is the last term.
Because the numbers are divisible by $7$, the common difference is $7$
The count of the numbers divisible by $7$ is the number of terms
$
(a.) \\[3ex]
a = 77 \\[3ex]
AP_n = 497 \\[3ex]
d = 7 \\[3ex]
n = ? \\[3ex]
AP_n = a + d(n - 1) \\[3ex]
497 = 77 + 7(n - 1) \\[3ex]
497 - 77 = 7(n - 1) \\[3ex]
420 = 7(n - 1) \\[3ex]
7(n - 1) = 420 \\[3ex]
n - 1 = \dfrac{420}{7} \\[5ex]
n - 1 = 60 \\[3ex]
n = 60 + 1 \\[3ex]
n = 61 \\[3ex]
$
There are 61 numbers between 75 and 500 that are divisible by 7
$
(b.) \\[3ex]
AP_n = a + d(n - 1) \\[3ex]
AP_8 = a + 7d \\[3ex]
AP_3 = a + 2d \\[3ex]
AP_7 = a + 6d \\[3ex]
AP_4 = a + 3d \\[3ex]
AP_8 = 5 * AP_3 \\[3ex]
a + 7d = 5(a + 2d) \\[3ex]
a + 7d = 5a + 10d \\[3ex]
5a + 10d = a + 7d \\[3ex]
5a - a + 10d - 7d = 0 \\[3ex]
4a + 3d = 0 ...eqn.(1) \\[3ex]
Also: \\[3ex]
AP_7 = 9 + AP_4 \\[3ex]
a + 6d = 9 + (a + 3d) \\[3ex]
a + 6d = 9 + a + 3d \\[3ex]
a - a + 6d - 3d = 9 \\[3ex]
3d = 9 \\[3ex]
d = \dfrac{9}{3} \\[5ex]
d = 3 \\[3ex]
Substitute \:\:d = 3\:\:into\:\:eqn.(1) \\[3ex]
4a + 3d = 0 \\[3ex]
4a = -3d \\[3ex]
4a = -3(3) \\[3ex]
4a = -9 \\[3ex]
a = -\dfrac{9}{4} \\[5ex]
AP_2 = a + d = -\dfrac{9}{4} + 3 = -\dfrac{9}{4} + \dfrac{12}{4} = \dfrac{-9 + 12}{4} = \dfrac{3}{4} \\[5ex]
AP_3 = a + 2d = AP_2 + d = \dfrac{3}{4} + 3 = \dfrac{3}{4} + \dfrac{12}{4} = \dfrac{3 + 12}{4} =
\dfrac{15}{4} \\[5ex]
AP_4 = a + 3d = AP_3 + d = \dfrac{15}{4} + 3 = \dfrac{15}{4} + \dfrac{12}{4} = \dfrac{15 + 12}{4} =
\dfrac{27}{4}
\\[5ex]
AP_5 = a + 2d = AP_4 + d = \dfrac{27}{4} + 3 = \dfrac{27}{4} + \dfrac{12}{4} = \dfrac{27 + 12}{4} =
\dfrac{39}{4}
\\[5ex]
AP:\:\: -\dfrac{9}{4}, \dfrac{3}{4}, \dfrac{15}{4}, \dfrac{27}{4}, \dfrac{39}{4}
$